Hyperandrogenism and insulin resistance‐induced fetal loss: evidence for placental mitochondrial abnormalities and elevated reactive oxygen species production in pregnant rats that mimic the clinical features of polycystic ovary syndrome. (3rd July 2019) - Zhang, Yuehui; Zhao, Wei; Xu, Hongfei; Hu, Min; Guo, Xiaozhu; Jia, Wenyan; Liu, Guoqi; Li, Juan; Cui, Peng; Lager, Susanne; Sferruzzi‐Perri, Amanda Nancy; Li, Wei; et al.
Abstract : Key points: Women with polycystic ovary syndrome (PCOS) commonly suffer from miscarriage, but the underlying mechanisms remain unknown. Herein, pregnant rats chronically treated with 5α‐dihydrotestosterone (DHT) and insulin exhibited hyperandrogenism and insulin resistance, as well as increased fetal loss, and these features are strikingly similar to those observed in pregnant PCOS patients. Fetal loss in our DHT+insulin‐treated pregnant rats was associated with mitochondrial dysfunction, disturbed superoxide dismutase 1 and Keap1/Nrf2 antioxidant responses, over‐production of reactive oxygen species (ROS) and impaired formation of the placenta. Chronic treatment of pregnant rats with DHT or insulin alone indicated that DHT triggered many of the molecular pathways leading to placental abnormalities and fetal loss, whereas insulin often exerted distinct effects on placental gene expression compared to co‐treatment with DHT and insulin. Treatment of DHT+insulin‐treated pregnant rats with the antioxidant N ‐acetylcysteine improved fetal survival but was deleterious in normal pregnant rats. Our results provide insight into the fetal loss associated with hyperandrogenism and insulin resistance in women and suggest that physiological levels of ROS are required for normal placental formation and fetal survival during pregnancy. Abstract: Women with polycystic ovary syndrome (PCOS) commonly suffer from miscarriage, but the underlying mechanism of PCOS‐induced fetal loss during pregnancy remains obscure and specific therapies are lacking. We used pregnant rats treated with 5α‐dihydrotestosterone (DHT) and insulin to investigate the impact of hyperandrogenism and insulin resistance on fetal survival and to determine the molecular link between PCOS conditions and placental dysfunction during pregnancy. Our study shows that pregnant rats chronically treated with a combination of DHT and insulin exhibited endocrine aberrations such as hyperandrogenism and insulin resistance that are strikingly similar to those in pregnant PCOS patients. Of pathophysiological significance, DHT+insulin‐treated pregnant rats had greater fetal loss and subsequently decreased litter sizes compared to normal pregnant rats. This negative effect was accompanied by impaired trophoblast differentiation, increased glycogen accumulation, and decreased angiogenesis in the placenta. Mechanistically, we report that over‐production of reactive oxygen species (ROS) in the placenta, mitochondrial dysfunction, and disturbed superoxide dismutase 1 (SOD1) and Keap1/Nrf2 antioxidant responses constitute important contributors to fetal loss in DHT+insulin‐treated pregnant rats. Many of the molecular pathways leading to placental abnormalities and fetal loss in DHT+insulin treatment were also seen in pregnant rats treated with DHT alone, whereas pregnant rats treated with insulin alone often exerted distinct effects on placental gene expression compared to insulin treatment in combination with DHT. We also found that treatment with the antioxidant N ‐acetylcysteine (NAC) improved fetal survival in DHT+insulin‐treated pregnant rats, an effect related to changes in Keap1/Nrf2 and nuclear factor‐κB signalling. However, NAC administration resulted in fetal loss in normal pregnant rats, most likely due to PCOS‐like endocrine abnormality induced by the treatment. Our results suggest that the deleterious effects of hyperandrogenism and insulin resistance on fetal survival are related to a constellation of mitochondria–ROS–SOD1/Nrf2 changes in the placenta. Our findings also suggest that physiological levels of ROS are required for normal placental formation and fetal survival during pregnancy. Key points: Women with polycystic ovary syndrome (PCOS) commonly suffer from miscarriage, but the underlying mechanisms remain unknown. Herein, pregnant rats chronically treated with 5α‐dihydrotestosterone (DHT) and insulin exhibited hyperandrogenism and insulin resistance, as well as increased fetal loss, and these features are strikingly similar to those observed in pregnant PCOS patients. Fetal loss in our DHT+insulin‐treated pregnant rats was associated with mitochondrial dysfunction, disturbed superoxide dismutase 1 and Keap1/Nrf2 antioxidant responses, over‐production of reactive oxygen species (ROS) and impaired formation of the placenta. Chronic treatment of pregnant rats with DHT or insulin alone indicated that DHT triggered many of the molecular pathways leading to placental abnormalities and fetal loss, whereas insulin often exerted distinct effects on placental gene expression compared to co‐treatment with DHT and insulin. Treatment of DHT+insulin‐treated pregnant rats with the antioxidant N ‐acetylcysteine improved fetal survival but was deleterious in normal pregnant rats. Our results provide insight into the fetal loss associated with hyperandrogenism and insulin resistance in women and suggest that physiological levels of ROS are required for normal placental formation and fetal survival during pregnancy.